Metody porządkowania liniowego w konstrukcji miernika oceny kapitału intelektualnego w przedsiębiorstwie - Staniec, Iwona (Linear Ordering Methods to Construction of Measure of Intellectual Capital in Enterprise, 2007)
Putting on intellectual capital is chance drastic reorientation in management presently and operations of each enterprises. It confirms financial results dynamically firms developing in the world, which base on knowledge activity and information. The aim this paper is purpose construction of measure of intellectual capital in enterprise with use linear ordering methods. It has given bases for structure these meters Hellwig.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 454-461